DESAIN EKSPERIMEN DALAM PENELITIAN PEMASARAN (Proceeding Fakultas Ekonomi, 2011)
In the field of marketing research, researchers can choose what research strategy to be used. Whether the researchers will use quantitative or qualitative methods? Whether the researcher will use survey methods or experiment? At this time in the field of marketing research, many researchers switched to using design of experiments. If we look at the survey and experiment turns each have advantages and disadvantages. Is the design of this experiment could solve marketing research? Experimentation is the objective observation of phenomena that are made to happen in a very controlled situation in which one or more factors left to vary while the other factors held constant. Experimental design has the advantage of having high internal validity, but instead a low external validity. This paper attempts to review how the experimental design, especially in marketing research.Keywords: marketing research, experimental design, survey, internal validity, external validity